Adiabatic hyperspherical study of weakly bound helium--helium--alkali-metal triatomic systems - Suno, Hiroya; Esry, B. D. (My University, 2010)
4He2–alkali-metal triatomic molecular systems are studied using the adiabatic hyperspherical representation. By adopting the best pairwise He-He and He-X interaction potentials, we search for weakly bound states of 4He2X systems with X=6Li, 7Li, 23Na, 39K, 40K, 41K, 85Rb, 87Rb, and 133Cs. We consider not only zero total angular momentum J=0 states, but also J>0 states. We find that the 4He62Li and 4He72Li systems each possess two bound states with JΠ=0+ symmetry and none with J>0, while the other 4He2–alkali-metal species are found to support one 0+ and one 1− bound state. We calculate the bound-state energies of these molecular species and discuss the essential features of the wave functions associated with these bound states.